Advances in fire retardant materials - Horrocks, A. Richard; Price, Dennis, Professor (Woodhead Pub., 2008)
Annotation This important book provides a comprehensive account of the advances that have occurred in fire science in relation to a broad range of materials. The manufacture of fire retardant materials is an active area of research, the understanding of which can improve safety as well as the marketability of a product.
" ... on behalf of the Institute of Materials, Minerals & Mining."
Keywords: Fire resistant materials.; Fireproofing of fabrics.; elektronické knihy; electronic books